UPAYA PENINGKATAN KETERAMPILAN PROSES SAINS PEMBELAJARAN IPA SISWA KELAS V MELALUI MODEL INKUIRI TERBIMBING DI SDN 02 KEUMUMU ACEH SELATAN - Fitri Wahyuni; Daniah; Wati Oviana (FITRAH: International Islamic Education Journal, 2023)
Students' science process skills in learning science at SDN 02 Keumumu Aceh Selatan are still very low. This is caused by several factors, such as the lack of using learning models that support the development of student KPS. One effort to overcome these problems is to use the guided inquiry model. This study aims to measure the improvement of students' science process skills in class V SDN 02 Keumumu Aceh Selatan through a guided inquiry model on the digestive organs of ruminants and humans. The method used was classroom action research (PTK). The data collection instruments used were teacher activity observation sheets, student activity observation sheets, student science process skills activity sheets. The data is calculated using the formula. The value obtained shows that teacher activity in cycle I, namely 70.83%, is in the "good" category and in cycle II, 89.42% has increased in the "very good" category, while student activity in the cycle, namely 59.78%, is in the category "Enough". And in cycle II it increases to the "very good" category with a score of 83.69%. The science process skills of students in cycle I, namely 58.90%, were in the "enough" category leading to cycle II with a value of 74.44%, which increased and entered the "good" category. Based on the problems that have been described, it can be said that the use of the guided inquiry model can improve science process skills in class V SDN 02 Keumumu Aceh Selatan.